MENELAAH EKSISTENSI MANUSIA DALAM PEMIKIRAN VITALISME NIETZSCHE - Putri, Endrika Widdia (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This paper examines the existence of humans in the vitalist thought of Nietzsche (1884–1900), one of the modern Western philosophers. This research is qualitative research using the descriptive analysis method. In this case, it attempts to describe and describe Nietzsche's vitalist thought and then analyzed it so that the desired results are obtained. This research shows data that in Nietzsche's view, the realization of the creativity of human existence is when humans can become the will to power